A Constrained High-pressure Control Equation for CO2 Heat Pump Water Heating System - Wang Lei; Liang Xingyu; Shao Liangliang; Zhang Chunlu (Zhileng xuebao)
The optimization and control of discharge pressure is important in transcritical CO2 heat pump water heating systems. The traditional high-pressure control equation simply takes the exit temperature of the gas cooler into account, neglecting the impacts of the pinch point and the outlet temperature of water, which might lead to a huge coefficient of performance (COP) loss in applications. In this paper, we report the development of a constrained gas cooler model by considering the influence of the pinch point and water inlet and outlet temperatures. The main impact factors of the optimum high pressure are determined through the design of experiments and statistical methods. Consequently, a new constrained optimal high-pressure control equation using least-squares regression is proposed. Based on the new control equation, the system COP loss is 1.8% in average (maximum 8.7%), providing better reliability for engineering practices.